2021
DOI: 10.1177/15330338211027898
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Drug Delivery by Na+/K+ ATPase α1 Targeting Peptide Conjugated DSPE-PEG Nanocarriers for Breast Cancer

Abstract: Although Epirubicin (EPI) is a commonly used anthracycline for the treatment of breast cancer in clinic, the serious side effects limit its long-term administration including myelosuppression and cardiomyopathy. Nanomedicines have been widely utilized as drug delivery vehicles to achieve precise targeting of breast cancer cells. Herein, we prepared a DSPE-PEG nanocarrier conjugated a peptide, which targeted the breast cancer overexpression protein Na+/K+ ATPase α1 (NKA-α1). The nanocarrier encapsulated the EPI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Micelles are already clinically tested to deliver anticancer drugs [53]. In particular, DSPE-PEG2000 micelles have been found to be effective in delivering a broad range of drugs in animal models [54][55][56][57] and RAD001 in vitro [58]. Properties such as a low critical micellar concentration as well as small size increase the appeal of DSPE-PEG2000 micelles since they can enable effective drug accumulation at the site of action [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Micelles are already clinically tested to deliver anticancer drugs [53]. In particular, DSPE-PEG2000 micelles have been found to be effective in delivering a broad range of drugs in animal models [54][55][56][57] and RAD001 in vitro [58]. Properties such as a low critical micellar concentration as well as small size increase the appeal of DSPE-PEG2000 micelles since they can enable effective drug accumulation at the site of action [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al has reported that, Epirubicin (EPI), upon entering the BC cells under the guidance of the targeting NKA-α1 peptide, exhibited a gradual release from the nanocarrier. 149 The controlled delivery and subsequent release of EPI within the BC cells resulted in significant inhibition of cell proliferation and migration in vitro and led to a substantial reduction in tumor volume in vivo. 149 The introduction of lumpectomy as a treatment for BC marked a significant advancement in disease management.…”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%
“… 149 The controlled delivery and subsequent release of EPI within the BC cells resulted in significant inhibition of cell proliferation and migration in vitro and led to a substantial reduction in tumor volume in vivo. 149 The introduction of lumpectomy as a treatment for BC marked a significant advancement in disease management. Onik in 2004 has suggested that a procedure akin to a “male lumpectomy”—one that precisely targets the cancerous portion of the prostate gland while minimizing patient morbidity—is indeed feasible.…”
Section: Ductal Carcinoma In Situ (Dcis)mentioning
confidence: 99%